Chemical composition and anti-inflammatory activity of n-butanol extract of Piper sarmentosum Roxb. In the intestinal porcine epithelial cells (IPEC-J2). (6th April 2021) - Wang, Dingfa; Zhou, Luli; Zhou, Hanlin; Hou, Guanyu
Abstract: Ethnopharmacological relevance: Piper sarmentosum Roxb. (PS) is a terrestrial herb primarily distributed in tropical and subtropical regions of Asia. It is widely used in folk medicine in certain countries of Southeast Asia for the treatment of fever, toothache, coughing and pleurisy, which showed the anti-inflammatory activity of PS. Aim of the study: This study aimed to investigate the chemical constituents and the molecular mechanism and related metabolic pathway by which n-butanol extract of PS (PSE-NB) exerts its anti-inflammatory effects. Materials and methods: Chemical constituents of PSE-NB was analyzed using ultrahigh-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) technique. Anti-inflammatory effects of PSE-NB were investigated in lipopolysaccharide (LPS)-induced IPEC-J2 cells. Results: In total, 218 compounds, including 94 alkaloids and 26 phenolics were tentatively identified, which indicating alkaloids and phenolics were the main constituents of PSE-NB. In addition, the current cell experiment in vitro showed that PSE-NB (10–500 μg/mL) pre-treatment before LPS stimulation significantly decreased mRNA expression of IL-1β, IL-6 and TNF-α in IPEC-J2 cells compared with LPS treatment ( p  < 0.05). PSE-NB improved mRNA expression of tight junction proteins ( ZO-1 and Occludin ) and NHE3, which were reduced by LPS stimulation ( p  < 0.05). Moreover, PSE-NB (10 μg/mL) alleviated LPS-induced protein expression of p65 and p-p65 ( p  < 0.05), and reduced p65 translocation into the nucleus induced by LPS. At the same time, metabolic pathway analysis indicated that PSE-NB exerts anti-inflammatory effects mainly via augmentation of methionine metabolism in IPEC-J2 cells. Conclusions: Taken together, the results suggested that alkaloids and phenolics were the main constituents in PSE-NB. PSE-NB might attenuate LPS-induced inflammatory responses in IPEC-J2 cells by regulating NF-κB signaling pathway and intracellular metabolic pattern. Graphical abstract: Image 1 Highlights: 218 compounds, including 94 alkaloids and 26 phenolics were tentatively identified. Alkaloids and phenolics are the main constituents in PSE-NB. PSE-NB might attenuate LPS-induced inflammatory responses in IPEC-J2 cells by regulating NF-κB signaling pathway and intracellular metabolic pattern.